New developments in occupational dermatology - Diepgen, Thomas L. (Journal der Deutschen Dermatologischen Gesellschaft, 2016)
Occupational skin diseases according to BK No. 5101 - “severe or recurrent skin diseases which have forced the person to discontinue all occupational activities that caused or could cause the development, worsening, or recurrence of the disease” - is the most commonly reported notifiable occupational diseases in Germany. Following the optimization of measures of primary, secondary, and tertiary prevention, today most individuals affected are able to continue their profession. With the revision of the German ordinance on occupational diseases (BKV) in January 2015, skin cancer caused by UV irradiation was added to the list of occupational diseases. The new occupational disease (BK) 5103 is defined as “squamous cell carcinoma or multiple actinic keratoses of the skin caused by natural UV irradiation”. In this context, “multiple” signifies the occurrence of either more than five individual actinic keratosis lesions over the course of 12 months or the presence of field cancerization of > 4 cm2. In the following review, important aspects of this new occupational disease will be highlighted and discussed.